Because We Are Christian and Filipino: Christianity and the Death Penalty in the Philippines - Cornelio, Jayeel (Social sciences and missions, 2021)
Abstract As part of his campaign against criminality, President Duterte has called for the reinstatement of the death penalty in the Philippines. Its most vocal supporters are evangelical and independent Christian leaders and lawmakers. Although a religious minority, these entities are politically influential. In this article we show that they support the death penalty because they are Christian and Filipino. They articulate their support in two respects: it is biblical and it must be administered on heinous crimes for the sake of innocent people. We unpack these statements in terms of a religious citizenship that disregards the reality of religious diversity in Philippine society.